The Urgency of Expanding Judges' Perspectives to Response of Enactment Adat Law in the Indonesian Criminal Code - Sari, Clara Mega Kharisma; Jamin, Mohammad (MultiTech Publisher, 2024)
Indonesia is a country of religious culture, and the enactment of Law No.1 of 2023 is an effort to decolonize and recognize and strengthen the existence of customary law in Indonesia. This research will explore the ability of judges in implementing Article 2 of the Law. This research adopts normative legal research using conceptual, statutory, and comparative approaches. The results of this study show that judges in Indonesia generally have a positivist view due to the limited views of judges. The recommendation from this research is for judges in Indonesia to explore, follow, and understand the laws that live in society. This needs to be done so that in determining a decision in accordance with the spirit, norms, values that exist in society and can realize an ideal customary criminal justice system, ideal customary criminal justice.